Pemanfaatan Canva sebagai Alat Desain Grafis dalam Mendukung Proyek Akademik: Studi Literatur dengan Studi Kasus Mahasiswa Universitas Negeri Yogyakarta - Reza, Yolandita Angga (Fakultas Komputer Dan Desain, 2025)
Graphic design is an important skill for students to support various academic and non-academic needs, such as making posters, presentations, and learning media. However, not all students have access or the ability to use professional design software that tends to be complex and takes time to learn. Canva, a user-friendly web-based graphic design platform, is here as an alternative that offers ease of use, high accessibility, and time efficiency. This study aims to analyze the use of Canva by students of Yogyakarta State University (UNY) in supporting their graphic design needs. The research method used is a literature study, with data collection from journals, books, and relevant reports about Canva as well as case studies of use by UNY students. The results of the study show that Canva is effectively used by UNY students, especially for simple design needs such as event posters and infographics. Canva's advantages include an intuitive interface, online collaboration capabilities, and ready-to-use templates. However, the limitations of advanced features and dependence on templates are obstacles for students who need more flexibility in design. This study recommends that students use Canva as a simple design solution, but still expand their skills by learning professional software. In addition, universities can integrate Canva training into student skill development programs. Further research is recommended to quantitatively explore user experience and measure the effect of Canva usage on student creativity.